Expression Analyses of Embryogenesis-Associated Genes during Somatic Embryogenesis of Adiantum capillus-veneris L. In vitro: New Insights into the Evolution of Reproductive Organs in Land Plants - Li, Xia; Han, Jing-Dan; Fang, Yu-Han; Bai, Shu-Nong; Rao, Guang-Yuan (Frontiers in Plant Science, 2017)
An efficient in vitro regeneration system via somatic embryogenesis was developed for a fern species Adiantum capillus-veneris. Adventitious shoots, green globular bodies (GGBs) and calli were obtained with the maximal induction rate on the Murashige and Skoog (MS) medium of low concentrations of 6-benzyladenine (BA) (0–1.0 mg/L), 2.0 mg/L BA without 2,4-dichlorophenoxyacetic acid (2,4-D), 0.5 mg/L 2,4-D and 0.5–1.0 mg/L 6-BA, respectively. Cyto-morphological and histological changes in the shoot development via calli and GGBs were examined. For a better understanding of these developmental events, expression patterns of six genes, AcLBD16, AcAGL, AcBBM, AcWUS, AcRKD and AcLEC1, were characterized during somatic embryogenesis. AcBBM and AcLEC1 were ubiquitously expressed in direct somatic embryogenesis (adventitious shoots and GGBs) the maximal expression of AcBBM in mature GGBs, and the high expression of AcLEC1 in GGB initiation and adventitious shoots. During the indirect somatic embryogenesis, AcLBD16, AcLEC1, AcRKD and AcWUS were highly expressed in mature calli. Additionally, phylogenetic analyses showed that AcWUS, AcBBM, AcLBD, AcAGL, AcRKD and their homologs of other green plants formed monophyletic clades, respectively. Some of these gene families, however, diversified rapidly with the occurrence of embryophytes, suggesting that embryogenesis-associated genes could experience a rapid evolution with the colonization of plants to terrestrial environments. Expression and phylogenetic analyses of those embryogenesis-associated genes by the aid of in vitro regeneration system of A. capillus-veneris provide new insights into the evolution of reproductive organs in land plants.